Safety and efficacy of blood exchange transfusion for priapism complicating sickle cell disease. Issue 1 (25th March 2015) - Ballas, Samir K.; Lyon, David
Abstract : Background : Priapism is unwanted painful penile erection that affects about 36% of boys and men with sickle cell disease (SCD) most of whom have sickle cell anemia. Clinically, priapism could be stuttering, minor, or major. The first two types are mild, last < 4 h, are usually treated at home, have good prognosis with normal sexual function. The major type of priapism lasts >4 h, associated with severe pain, requires hospitalization; often does not respond to medical treatment and may require shunt surgery. Untreated major priapism and surgical intervention often cause impotence. In this study, we report our 15‐year experience in treating adult patients with SCD and major priapism with blood exchange transfusion after being refractory to other medical therapies.Methods : Adult male African Americans patients with SCD and major priapism were enrolled in this study and followed for 15 years. A Haemonitics V‐50 machine was initially used for whole blood exchange and was later replaced with Cobe Spectra machine for RBC exchange.Results : We used 239 blood exchanges requiring 1, 136 RBC units. We maintained a post‐exchange hemoglobin level of about 10 g/dL and hemoglobin S level < 30%. None of the patients had any neurological complications such as headache, seizures, neurological deficits, or obtundation post‐exchange.Conclusion : Together, the data indicate that blood exchange transfusion for the treatment of patients with SCD and major priapism is efficacious and safe. J. Clin. Apheresis 31:5–10, 2016. © 2015 Wiley Periodicals, Inc.